Sizing of Hybrid Photovoltaic-Wind Energy Systems Based on Local Data Acquisition (2021)
Although there are different alternatives to provide energy, there are still remote regions with no nearby possibilities of having an electricity supply that meets their basic needs. Colombia, like many countries, does not have uniform environmental conditions; therefore, applying models for the dimensioning of energy systems based on renewable energy can be inefficient and expensive, making it difficult to access electricity in isolated places. The research aims to develop a sizing strategy for a hybrid system based on locally acquired environmental information to size a system that takes advantage of the natural resources available in the local in the best possible way. Information is collected through a data acquisition system on local environmental conditions, system requirements are established based on energy demand, and a mathematical model is sought that represents the electrical behavior. The model makes it possible to analyze the system’s behavior under variable environmental conditions in the region, thus guaranteeing an adequate dimensioning for a constant supply of low-power energy suitable for residential use. This article presents an alternative to characterize a hybrid power generation system (photovoltaic/wind turbine) through data collected on-site, which, when properly processed, allows the dimensioning of a more appropriate hybrid system to the environmental conditions the environment. The system was implemented in an experimental farm of the University of Pamplona located in the north of Colombia. Based on this strategy, a hybrid system was designed and installed to meet energy demands efficiently.